Mean reversion: an investigation from Karachi stock exchange sectors - Vveinhardt, Jolita; Streimikiene, Dalia; Rizwan, Ahmed Raheem; Nawaz, Ahmad; Rehman, Aniqe (Technological and Economic Development of Economy, 2016)
This article analyses the sectors of Karachi stock exchange in order to determine if there is any presence of mean reversion phenomenon in the stock market sectors and also an attempt to determine the pace of mean reversion. To conduct this research, secondary data is collected from the State Bank Bulletin. The frequency of the data is monthly. The variables include the individual; the data was obtained from 24 sectors returns over the period of 17 years from January 1992 to June 2008. The GARCH (1, 1) model was used to find the outcomes and the effects. In the two sectors out of 24 sectors, the GARCH and ARCH effects were significant, namely, in the Jute and Banks & Investment Companies. We studied the mean reverting process in the KSE sectors over a specific time period. Since, the mean reversion varies over different time periods. Therefore, it would be a good area for future research to study the reasons, why the market reacts differently over different time periods and to determine the reasons for such variations. The paper contributes to Stock Prices returns and investment opportunities by studying the Mean Reversion Phenomenon.